Ð£Ð»ÑŒÑ‚Ñ€Ð°ÑÑ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ð½Ñ‹Ðµ Ð¿ÐµÑ€ÐµÑÑ‚Ñ€Ð¾Ð¹ÐºÐ¸ Ð¼Ð¸Ð¾ÐºÐ°Ñ€Ð´Ð° Ð¼Ð¾Ð»Ð¾Ð´Ñ‹Ñ… Ð¸ ÑÑ‚Ð°Ñ€Ñ‹Ñ… ÐºÑ€Ñ‹Ñ Ð¿Ð¾ÑÐ»Ðµ ÑÐºÑÑ‚Ñ€ÐµÐ¼Ð°Ð»ÑŒÐ½Ð¾Ð¹ ÐºÑ€Ð¸Ð¾Ñ‚ÐµÑ€Ð°Ð¿Ð¸Ð¸ - Babijchuk, V. G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
The effect of extreme low temperatures (â€“120Â°C) in young and aged rats on dynamics of ultrastructural re-arrangement of cardiomyocytes and endotheliocytes of myocardium capillaries depending on the number of cooling sessions was studied. After 9 cooling sessions in cryochamber in young rats there was found the development of ultrastructural re-arrangements characteristic for an increased activity of intracellular metabolic processes, which is structurally expressed in a rise in the number of mitochondria cristas, amount of decondensated chromatin, glycogen granules, ribosomes and polysomes. In architecture of cardiomyocytes of aged rats after cooling there were noted the re-arrangements of compensatory type: an increase in the number of mitochondria and cristas in them, lessening of the number of destruction and degeneration mitochondria foci. In sarcoplasm the number of ribosomes and polysomes, glycogen, that points to a rise in metabolic activity of cardiomyocytes. The quantity of mitochondria with membrane destructions decreases. Activity of transcellular transport of substances that is confirmed with the rise in the quantity of micropinocytotic vesicles in cytoplasm of endotheliocytes of out-growings. Analysis of change in ultrastructure of myocardium emphasizes the possibility of using cryotherapy as stimulating factor increasing functional activity of myocardium.